Effects of Notch signaling pathway inhibition by dibenzazepine in acute experimental toxoplasmosis. (December 2022) - Briceño, Marisol Pallete; Cariaco, Yusmaris; Almeida, Marcos Paulo Oliveira; Miranda, Natália Carnevalli; Araujo, Ester Cristina Borges; Santos, Sofia Nascimento; Bernardes, Emerson Soares; Silva, Neide Maria
Abstract: Notch signaling pathway plays a crucial role in cellular fate across species, being important for the differentiation and development of several cell types. The aim of this study was to evaluate the effect of Notch inhibition pathway by dibenzazepine (DBZ) in histological and inflammatory alterations and, tissue parasitism in acute Toxoplasma gondii infection. For this, C57BL/6 mice were treated with DBZ before infection with T. gondii, and the small intestine, lungs and liver were analyzed. The genes related to Notch signaling pathway were assayed through qPCR in the organs, and cytokine measurement was performed in serum samples. In the small intestine, T. gondii infection impaired the Hes1 and Math1 mRNA expressions, increased the inflammation and decreased goblet and Paneth cell numbers. The DBZ-treatment was able to partially preserve these cells, however, the parasitism and inflammation were not altered. In parallel, the high IL-2, IL-6, TNF and, IFN-γ levels induced by infection were not changed with the DBZ treatment, with the IFN-γ levels even higher. In contrast, in the liver and lungs, the DBZ-treatment diminished parasitism and inflammation. Our results highlight that Notch pathway inhibition in T.gondii infection results in different parasitological and inflammatory outcomes depending on the organ analyzed. Graphical Abstract: ga1 Highlights: T. gondii infection decreased Hes1 and Math1 mRNA in the small intestine. Dibenzazepine-treatment does not influence intestinal parasitism and inflammation. DBZ preserves partially the goblet and Paneth cell numbers in the small intestine. DBZ-treatment diminished the parasitism and inflammation in the lungs and liver.